PENGAWASAN PEMERINTAH DAERAH TERHADAP PELAKSANAAN BELANJA DESA (STUDI KASUS DI KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU TAHUN 2016) - Ilham Akbar; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The research was conducted at the Office of Community Empowerment and Village Government of Indragiri Hulu Regency, Inspectorate Office of Indragiri Hulu Regency, Rakit Kulim District Office, then in Kelayang Village, Kota Baru Village and Kampung Bunga Village. The purpose of this study is to determine the implementation of supervision and supervision mechanisms conducted by the Government of Indragiri Hulu Regency to the implementation of village spending in Rakit Kulim District Year 2016 and to determine the factors that cause villages in Kecamatan Rakit Kulim can not do village expenditure in maximum. The type of data used in this study is primary data and secondary data with the number of informants amounted to 13 people. The technique of taking informants in this research is by Purposive Sampling technique. as for data analysis techniques used in this research is with descriptive data analysis techniques. Based on the results of research that the authors do can be concluded that the Supervision of Local Government Indragiri Hulu Against Village Expenditure in the District of Rakit Kulim Year 2016 not yet maximized, this is based on 3 mechanisms of supervision conducted by the Government of Indragiri Hulu Regency in overseeing the village shopping activities that is 1) Monitoring of realization report of APBDes implementation found deviation in indirect expenditure such as expenditure for salary and operational of village administration has passed maximum limit,(2) supervision done by Auditing on the realization report of APBDes implementation for the villages in District Rakit Kulim Year 2016 has never been done by the Inspectorate of Indragiri Hulu Regency, (3) The supervision conducted by conducting Direct Observation is also not yet maximal for villages in District Rakit Kulim in 2016 due to the lack of budget and limited number of personnel required by BPMPD and Inspectorate of Indragiri Hulu. As for the factors that caused the villages in District Rakit Kulim in 2016 not only the maximum of village expenditure by low of human resources owned by village government, and low of public participation.Keywords: Supervision, Local Government, Village Expenditure.